Clinical Outcomes of Ahmed ClearPath Implantation in Glaucomatous Eyes: A Novel Valveless Glaucoma Drainage Device. Issue 5 (7th May 2022) - Grover, Davinder S.; Kahook, Malik Y.; Seibold, Leonard K.; Singh, Inder Paul; Ansari, Husam; Butler, Michelle R.; Smith, Oluwatosin U.; Sawhney, Gagan K.; Van Tassel, Sarah H.; Dorairaj, Syril
Abstract : Précis: Designed with novel features to facilitate implantation and improve safety, the Ahmed ClearPath (ACP) glaucoma drainage device (GDD) provided intraocular pressure (IOP) reduction comparable with other GDDs in eyes with refractory glaucoma in a multicenter retrospective study. Purpose: To present clinical outcomes with a novel valveless GDD (ACP, New World Medical). The 250 and 350 mm 2 models feature a contoured plate for optimal globe apposition, anteriorized suture points to facilitate suturing to the globe, and a prethreaded 4-0 polypropylene ripcord suture. Methods: This was a multicenter retrospective analysis of eyes with medically and/or surgically uncontrolled glaucoma implanted with the 250 or 350 mm 2 ACP either as a standalone procedure or in combination with other procedures. Pre-, intra-, and postoperative data through 6 months were collected. Results: A total of 104 eyes (100 subjects) received the ACP by 10 US surgeons, 63.5% of which had primary open-angle glaucoma and 62.5% had severe glaucoma. Mean baseline IOP was 26.3 (9.0) mm Hg and mean medication use was 3.9 (1.3). Through 6 months' follow-up, mean IOP ranged from 13.6 to 16.7 mm Hg and mean medication use from 0.9 to 1.9 medications ( P <0.0001 at all timepoints for each outcome measure). At 6 months, mean IOP was 13.7 mm Hg (−13.0 mm Hg, 43.0%, P <0.0001) and mean medication use was 1.9 medications per eye (−2.1, 47.7%, P <0.0001). Common adverse events included anterior chamber inflammation (16.3%), hyphema (15.4%), and hypotony (6.7%). Conclusion: The new ACP appears to be safe and efficacious as a standalone procedure or in combination with other procedures for uncontrolled glaucoma, and may be considered as a GDD option for patients in whom its unique design may facilitate the implantation process.